Utilization of a Guideline-recommended Imaging Paradigm for Pregnant Patients With Suspicion of Pulmonary Embolism. Issue 1 (20th January 2023) - McCandlish, John A.; Naidich, Jason J.; Feizullayeva, Chinara; Makhnevich, Alexander; Barish, Matthew A.; Sanelli, Pina C.; Cohen, Stuart L.
Abstract : Purpose: A dose reduction imaging paradigm utilizing chest x-ray (CXR) to triage between computed tomography pulmonary angiography (CTPA) and lung scintigraphy (LS) was introduced in 2001 and adopted in 2012 by the American Thoracic Society/Society of Thoracic Radiology (ATS) guideline for the evaluation of pulmonary embolism in pregnancy. We aimed to assess the utilization of this imaging paradigm preadoption and postadoption by the ATS guideline, and identify factors associated with its utilization. Materials and Methods: This retrospective cohort study evaluated consecutive pregnant patients who received CTPA or LS for the evaluation of pulmonary embolism in pregnancy at 2 tertiary hospitals between September 2008 and March 2017, excluding 2012 for guideline release washout. Utilization of the imaging paradigm was defined per patient by the use of CXR before advanced imaging, with CTPA performed following positive CXR and LS performed following negative CXR. Multivariate analyses were performed to assess factors associated with utilization of the imaging paradigm. P <0.05 is considered significant. Results: Overall, 9.8% (63/643) of studies utilized the dose reduction imaging paradigm, 13.3% (34/256) before the guidelines, and 7.5% (29/387) after. Multivariable analysis showed that the dose reduction imaging paradigm utilization was higher for inpatients (odds ratio [OR]: 4.5) and outpatients (OR: 3.1) relative to the emergency department patients, and lower for second (OR: 0.3) and third (OR: 0.2) trimester patients, without significant differences by study priority, patient age, or patient race. Conclusions: Guideline-recommended dose reduction imaging paradigm utilization was low, and decreased after guideline publication. Utilization varied by patient setting and trimester, which are potential targets for interventions to improve guideline compliance.